Analisis Kesenjangan Keterampilan Digital dalam Pengembangan Smart City - Siti Alayda Azzahro; Muhayat Muhayat; Febi Novia Putri (Pusat Riset dan Inovasi Nasional, 2026)
The paradigm of urban planning has undergone drastic changes due to the digital transformation, shifting toward a smart city model supported by big data, artificial intelligence, information technology, and integrated digital systems. However, human resource readiness and digital competencies are just as important as technological infrastructure for the success of smart city development efforts. Through an Integrative Literature Review (ILR), this study aims to synthesize the conceptual history, multidimensional causes, and governance implications related to the digital skills gap in smart city development. Thematic synthesis and comparative mapping were used to comprehensively evaluate 25 journal articles indexed by Scopus. According to the study’s findings, the digital skills gap has evolved from a mere labor market mismatch into a multifaceted governance challenge, encompassing technological, institutional, societal, leadership, and ethical dimensions. This study also demonstrates how the digital skills gap impacts data-driven governance, a smart city’s capacity for innovation, digital inclusion, and socio-economic equity. It highlights digital capacity as a strategic prerequisite for smart city development by integrating disparate literature into a single analytical framework. This study makes a theoretical contribution by integrating digital governance, inclusive smart city concepts, and skills gap theory into a logical conceptual model.